Hey there! :)
Answer:
y = 11.
Step-by-step explanation:
Set both of the equations equal:
5x - 9 = x² - 3x + 7
Rearrange the equation:
0 = x² - 3x - 5x + 9 + 7
Combine like terms:
0 = x² - 8x + 16
Factor:
0 = (x -4)²
Solve for x:
0 = x - 4
x = 4.
Plug this into an equation to solve for 'y':
y = 5(4) - 9
y = 20 - 9
y = 11.
For this case we have the following expression:
By definition, a coefficient is the term that accompanies one or more variables.
For example:
The coefficient of the linear term is 3.
So, in the given expression we have to:
-4 is the term that accompanies the variables xy.
Answer:
-4
Let 4 + 3x = u
then 3dx = du
or, <span>1/3∫<span>u√</span>du
</span>
= <span>1/3<span>u^<span>3/2</span></span>/(3/2)
</span>
= <span>2/9∗(4+3x<span>)^<span>3/2
I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!
</span></span></span>
Answer:
=6
Step-by-step explanation:
(5×8)×(5-2)/(5×4)
Numerator =40×3
=120
Denominator = 5×4
=20
simplifying 120/20
=6